Mechanical properties of mitral allografts are not reasonably influenced by cryopreservation in sheep model - Hlubocký, J; Mokráček, A; Nováček, V; Vojáček, J; Burkert, J; Kochová, P; Klepáček, J; Pepper, J; Spatenka, J (Physiological research, 2011)
A mitral allograft is used exceptionally in the mitral, as well as in the tricuspid position, mostly as an experimental surgical procedure. The authors decided to evaluate the possibility of inserting a cryopreserved mitral allograft into the tricuspid position in a sheep experimental model. Within the framework of this experimental project the mechanical properties of the cryopreserved mitral allograft were tested. A novel methodology studying the functional unit composed of mitral annulus, leaflet, chordae tendinaea, and papillary muscle is presented. A five-parameter Maxwell model was applied to characterize the viscoelastic behavior of sheep mitral valves. A control group of 39 fresh mitral specimens and a test group of 13 cryopreserved mitral allografts from tissue bank were tested. The testing protocol consisted of six loading cycles with 1 mm elongation every 5 min. There was no significant difference in the mean values of the determined parameters (p>0.05) which confirms the main hypothesis that cryopreservation does not influence significantly material parameters characterizing the tissue mechanics. Slight discrepancy is observed in variances of viscous parameters suggesting that the values of the test group may be spread over larger interval due to the treatment.
Keywords: Cryopreservation; mechanický stres; povrchové vlastnosti; Surface Properties; modely u zvířat; Animals; Sheep; Tricuspid Valve; zvířata; Mitral Valve; Heart Valve Prosthesis; ovce; Stress, Mechanical; srdeční chlopně umělé; Models, Animal; kryoprezervace; trikuspidální chlopeň; mitrální chlopeň